VITAMIN D PADA KEHAMILAN - Arif Sabta Aji (ARGIPA (Arsip Gizi dan Pangan), 2016)
Vitamin D defciency or insuffciency, including global public health problem. VitaminD status in pregnancy plays an important role on maternal and fetal health. Beside the classicalrole in bone and mineral metabolism, vitamin D and vitamin D receptor gene (VDR) is the keystimulating the proliferation and differentiation approximately 200-300 genes, which many ofthem regulate fetal development, it makes vitamin D important in pregnancy. The aim of thisreview is to explain how vitamin D-related implications on maternal and fetal health. Manyof the research concentration 25(OH)D serum levels is associated with pregnancy outcomes74 Volume 1, Nomor 2, Julii─Desember 2016such as preeclampsia, Gestational Diabetes Mellitus, Caesar birth delivery, bone health,preterm birth, intra uterine growth retardation, small for gestational age, and low birth weight.Pregnant mothers need higher vitamin D than usual. Therefore, a recommendation of vitaminD supplementation is needed for pregnant mothers who are defcient, safe and effective dose is4000 IU/day. The main source of vitamin D is most effective sun exposure UVB (90%) andfood (10%). The main determining factors affecting vitamin D status were the lifestyle, sunexposure behavior (use of sunblock, clothes, latitude, sunscreens) and low food intake of vitaminD. Therefore, women who undergo frst antenatal care recommended to be given informationregarding the importance of the role of vitamin D during pregnancy for maternal and fetalhealth.